THE SEARCH FOR THE PAST: THE ROLE OF AZTEC MYTHOLOGY IN LA REGIÓN MÁS TRANSPARENTE - Williams, Shirley A. (Estudos Ibero-Americanos, 1976)
Carlos Fuentes' use of Aztec mythology in La región más transparente has a far more important function than simply creating an exotic and uniquely Mexican atmosphere for his national epic. Fuentes' use of indigenous mythology and symbolism, especially his novelistic transforrnation of the Aztec fire rites, is intimately related to the development of one of the novel's central themes - the rise and fall of Federico Robles. Only through understanding the significance of the Aztec fire rites can the reader fully understand Robles' destruction and subsequent rebirth. SAW